2021
DOI: 10.1088/1755-1315/746/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Introduced Species of Fishes in Penjalin Reservoir Central Java Indonesia

Abstract: The decreased diversity of fish is partly due to the introduction of fish or foreign species into the waters. The impact of this entry is relatively vast, not only damaging the environment and genetic but also disturbing the indigenous species and spreading disease and parasites to the fish. This study aimed to analyze the fish diversity of introduced species and indigenous species captured in Penjalin Reservoir and the correlation between biodiversity and water quality. The method included a survey with five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The biodiversity of fish in the inland waters of Sulawesi in 2004 showed that the composition of fish was dominated by the fish species introduced [6,7]. [8,9] describes Indonesia as the number three megabiodiversity country in the world with 1,193 species of fish with 120 endemic fish species. Indonesian freshwater fish inhabit three geographic distribution areas (Sundanese, Wallace, and Sahul) bounded by two virtual lines: the Wallace Line and the Weber Line which have their species characteristics [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The biodiversity of fish in the inland waters of Sulawesi in 2004 showed that the composition of fish was dominated by the fish species introduced [6,7]. [8,9] describes Indonesia as the number three megabiodiversity country in the world with 1,193 species of fish with 120 endemic fish species. Indonesian freshwater fish inhabit three geographic distribution areas (Sundanese, Wallace, and Sahul) bounded by two virtual lines: the Wallace Line and the Weber Line which have their species characteristics [8,10].…”
Section: Introductionmentioning
confidence: 99%